Desenvolvimento de habilidades de consciência fonológica: independência e interdependência funcional no repertório de leitores iniciantes - Freitas, Fabiana Rego (2008)
The sensibility to sound structure of oral language is characterized as the development of abilities of phonological awareness, which have been categorized as rhyme and onset skills, syllabic skills and phonemic skills (the latter two are subcategorized into synthesis, analysis, manipulation and transposition). Studies demonstrated bidirectional relation between phonological awareness and acquisition of reading. However, treating all the skills together, is unclear how each one develops; if each one is or is not independent of the others and if the development of ones can affect the development of another. The purpose of this study was to promote the teaching of phonological awareness at six elementary school children and verify the progress development of each skill, taught separately and sequentially, through a teaching program designed. A multiple baseline design between abilities was employed to assess possible effects of each one ability to another. The 10 abilities were assessed individually before start the program and after the teaching of each one. The Phonological Awareness Test was applied before and at the final of the program instruction and adaptations of it (developed by the experimenter) were implemented after the teaching of each skill. The tasks were conducted in a playful environment, with colorful and manipulated material to represent sounds. All participants showed a considerable development of abilities that were missing or incipient in the first assessment. The multiple baseline design showed a high degree of functional independence between abilities, suggesting that each skill can be acquired independently of the others. This study thus provided a contribution to the refinement conceptual and a methodological contribution. The results showed little interference for one ability to the others, indicating to a possible functional independence between abilities, suggests the importance of systematic teaching and assessing of each one and all abilities, to ensure their complete development. On the other hand, this study raises the question of whether appropriate conditions for procedures could promote the development of interdependence between abilities, to become the teaching more effective and economic, without the necessity of each one discrimination ability involved in phonological awareness.